2016
DOI: 10.3233/bmr-160694
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of upper extremity circuit resistance training on muscle strength and functional independence in patients with paraplegia

Abstract: Randomized trial (Level II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Muscle strength is a highly relevant fitness outcome in the chronic SCI population, as improvements in strength have a significant impact on the ability to perform activities of daily living [ 26 ]. The research analyzing the effects of progressive resistance exercises (PREs) and endurance exercises (EEs) on upper extremity in patients with paraplegia [ 28 , 29 ] confirms its importance in increasing activities of daily living (ADLs) in patients with spinal cord injury (SCI).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength is a highly relevant fitness outcome in the chronic SCI population, as improvements in strength have a significant impact on the ability to perform activities of daily living [ 26 ]. The research analyzing the effects of progressive resistance exercises (PREs) and endurance exercises (EEs) on upper extremity in patients with paraplegia [ 28 , 29 ] confirms its importance in increasing activities of daily living (ADLs) in patients with spinal cord injury (SCI).…”
Section: Discussionmentioning
confidence: 99%
“…One research group previously applied 12 weeks of circuit training three times a week and reported a 12%–30% increase in the muscle strength for all movements [ 20 ]. Similarly, another group applied 6 weeks of resistance circuit training and reported significant improvements in elbow flexion and extension strength in the experimental group [ 21 ]. In another study, women over 60 years of age received 10 weeks of circuit training (three times per week) and significant improvement in the participants’ muscle strength and muscular endurance (27.8%–40%) was observed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CTE may help to increase upper extremity strength in patients with paraplegia. [ 9 - 13 ] Yildirim et al[ 13 ] reported that upper extremity strengthening exercises using mechanical exercise stations combined with the conventional rehabilitation were useful in terms of increasing the strength and improving the physical disability as measured by the Functional Independence Measure in the persons with paraplegia. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Circuit training exercises (CTEs) help to improve upper extremity muscle strength and endurance in SCI. [ 9 - 13 ] There are limited studies in SCI patients with elastic bands. [ 9 , 14 ] The elastic bands are used for CTE, as they are inexpensive and easy-to-use.…”
Section: Introductionmentioning
confidence: 99%